2020
DOI: 10.1007/s00300-020-02651-0
|View full text |Cite
|
Sign up to set email alerts
|

Response of dimethylsulfoniopropionate (DMSP) and dimethylsulfoxide (DMSO) cell quotas to salinity and temperature shifts in the sea-ice diatom Fragilariopsis cylindrus

Abstract: Sea ice is an extreme environment known to host microbial communities which produce high concentrations of the metabolites dimethylsulfoniopropionate (DMSP) and dimethylsulfoxide (DMSO). These two compounds are involved in the cycling of the climate cooling gas dimethylsulfide (DMS). Despite decades of research, the drivers of these large concentrations in sea ice remain largely unknown. In this study, we use a cell culture approach to quantify for the first time the DMSP and DMSO cell quotas for the diatom Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 87 publications
(115 reference statements)
2
10
0
Order By: Relevance
“…Also, we preferred the experiment at S75 and -2.4°C to the one at S75 and 4°C to obtain the conditions closest to those encountered by algae in situ. Whatever the temperature, results obtained at S75 were similar for both algae (Fig.3 and Wittek et al (2020)).…”
Section: Empirical Relationssupporting
confidence: 59%
See 2 more Smart Citations
“…Also, we preferred the experiment at S75 and -2.4°C to the one at S75 and 4°C to obtain the conditions closest to those encountered by algae in situ. Whatever the temperature, results obtained at S75 were similar for both algae (Fig.3 and Wittek et al (2020)).…”
Section: Empirical Relationssupporting
confidence: 59%
“…In this simplistic approach, we postulated that the taxonomic composition in sea ice was restricted to two major groups: diatoms and flagellates (including Phaeocystis sp., dinoflagellates and other flagellates). Hence, for our calculation, we considered that the production of DMSP and DMSO by the group of diatoms could be estimated through the empirical relations from our experiment on F.cylindrus (Wittek et al 2020) and the DSC production of flagellates by the P.antarctica empirical relations (this study).…”
Section: Estimation Of Natural Dsc Brines Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study conducted in N. tabacum plants, short-term and low-dose SS induced metabolic shifts toward gluconeogenesis, which involved accumulation of mainly glucose, sucrose and fructose with depletion of pyrimidine and purine metabolites, while a high-dose of salt increased the accumulation of the osmolytes proline, myo-inositol and GABA [ 61 ]. Dimethylsulfoniopropionate (DMSP) is produced by a large diversity of macroalgae [ 110 ] and has a significant impact on SS and temperature shifts [ 111 , 112 ]. Intracellular functions of DMSP are not well understood but this molecule has been proposed to act as an osmoregulator [ 113 ] and antioxidant [ 114 ].…”
Section: Metabolic Reprogramming In Plants Responding To Ssmentioning
confidence: 99%
“…These results suggested that DMSP and DMSO might play a role in SS responses and help F . cylindrus to counterattack increased salinity levels [ 112 ]. The above studies and the additional studies detailed in Table 1 demonstrate that reprogramming of PMs in plants are an adaptive response for survival under SS.…”
Section: Metabolic Reprogramming In Plants Responding To Ssmentioning
confidence: 99%